Effect of high temperature stress on the performance of twelve sweet pepper genotypes (Bangladesh Journal of Agricultural Research, 2010)
A study on heat tolerance in sweet pepper was conducted at the Asian Vegetable Research and Development Centre (AVRDC), Taiwan from December 1999 to May 2000. Experiments were carried out to investigate the influence of 29/23°C and 24/18°C stress on 12 sweet pepper genotypes on growth, development, reproductive behaviour and yield potentialities and to verify the results of the phytotron study. Performance of 12 sweet pepper genotypes was evaluated under two different temperature regimes of 24/18° C and 29/23° C in the phytotron. Plant height was found higher at 29/23° C compared to 24/18° C. High temperature reduced percent fruit set as well as size of fruits. Individual fruit weight was higher (7.44-125.00 g) when grown at 24/18°C and lower (5.35-103.80 g) at 29/23°C. Out of 12 genotypes, SP00l, SP002, SP004, and SP012 performed poor in respect of per plant yield at higher temperature compared to the lower temperature. So, these four genotypes were considered to be heat sensitive than the others. Leaf proline content of the sensitive genotypes decreased under the high temperature conditions and the heat tolerant lines produced higher amount of proline indicating the role of proline in expressing the heat tolerant capability of sweet pepper genotypes concerned. Keywords: High temperature stress; performance; sweet pepper. DOI: 10.3329/bjar.v35i3.6459Bangladesh J. Agril. Res. 35(3) : 525-534